Long-range temporal correlations in the Kardar–Parisi–Zhang growth: numerical simulations. (16th November 2016) - Song, Tianshu; Xia, Hui
Abstract: To analyze long-range temporal correlations in surface growth, we study numerically the (1 + 1)-dimensional Kardar–Parisi–Zhang (KPZ) equation driven by temporally correlated noise, and obtain the scaling exponents based on two different numerical methods. Our simulations show that the numerical results are in good agreement with the dynamic renormalization group (DRG) predictions, and are also consistent with the simulation results of the ballistic deposition (BD) model.